Design of the Monitoring System for Subway Platform Screen Doors Based on CAN Bus - Caiqi Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In this paper, the application layer communication protocol of CAN bus and the monitoring system for subway platform screen doors are proposed. The system framework is built, hardware of every function module for this system is selected, and the monitoring platform of epigynous machine is designed. On the basis of the above work the communication function of the monitoring system is realized, and specific flowchart is given. This system has been tested at a subway line in Shanghai. And the results prove that the system is in full compliance with industry standards and can completely meet the application requirements. The architecture plan of the system is practically proven to be valid and feasible.